PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR KOGNITIF SISWA PADA MATA PELAJARAN EKONOMI KELAS X SMA SWASTA TAMAN SISWA PEMATANGSIANTAR - LIA. S; Tumpal Manahara M. Siahaan; Herlina Hotmadinar Sianipar (JURNAL ILMIAH NUSANTARA, 2024)
This study aims to prove the influence of learning model strategies Problem Based Learning on the cognitive learning outcomes of students in economics class X of Tamansiswa Private High School Pematangsiantar. The problem in this study is the economic learning outcomes on the material of distribution and consumption economic activities using the learning model strategy Problem Based Learning and models Teacher Centered Learning class X at Tamansiswa Private High School Pematangsiantar.This type of research is quantitative research. The population in this study is all students of class X of Tamansiswa Private High School Pematangsiantar with a total of 283 students. The sample in this study consists of 2 classes, namely class X Merdeka 3 and class X Merdeka 4 with a total of 71 students.Based on the results of descriptive analysis, it shows that the average economic learning outcomes in the material of economic activities, distribution, and consumption in classes that do not use the learning model strategy Problem Based Learning which is 72.70. Meanwhile, the average learning outcomes of students in classes that use learning model strategies Problem Based Learning which is 79.71. In the data analysis technique, the hypothesis test "t" is 5.277 ˃ 1.995 It can be concluded that it is accepted and rejected, meaning that there is an influence of the Problem Based Learning learning model on students' cognitive learning outcomes in Economics subjects.